Clean Jobs, Dirty Jobs: Ethnicity, Social Reproduction and Gendered Identity - Giles, Wenona (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1993)
Issues of ethnic identity, gender and politics intersect for two generations of Portuguese women in Toronto. In this article I use a ’social reproduction’ approach to analyze the meaning of exploitation for these women. The co-existence of both resistance to the dominant hegemonic culture and appropriation of nativistic notions of progress among the two generations of women are examined. The use of the words ’clean’ and ’dirty’ as they pertain to wage work and issues of status and ethnic identity are explored.